Protocol for the CUPIDO trials; multicenter randomized controlled trials to assess the value of combining prolapse surgery and incontinence surgery in patients with genital prolapse and evident stress incontinence (CUPIDO I) and in patients with genital prolapse and occult stress incontinence (CUPIDO II) - van der Vaart Huub; Dijkgraaf Marcel GW; van der Ploeg Marinus; van der Steen Annemarie; Roovers Jan-Paul WR (BMC, 2010)
Abstract Background About 40% of all patients with genital prolapse report stress-incontinence. In about half of the 60% patients that do not report stress-incontinence, occult urinary stress-incontinence can be detected. In these patients stress-incontinence is masked due to kinking or compression of the urethra by the prolapse. In case surgical correction is indicated there are two strategies to manage patients with combined prolapse and (occult) stress incontinence. This strategy is either (i) a combination of prolapse surgery and stress-incontinence surgery or (ii) to correct the prolapse first and evaluate afterwards whether additional stress-incontinence surgery is indicated. The advantage of combining prolapse and stress-incontinence surgery is that only few patients report stress-incontinence following such combination. However, this combination has been associated with an increased risk on complications, of which the development of obstructive micturition symptoms, overactive bladder symptoms and bladder retention are the most important ones. Furthermore, combining two procedures may be unnecessary as performing only prolapse surgery may cure stress-incontinence In the randomized CUPIDO trials both strategies are compared in patients with prolapse and evident stress incontinence (CUPIDO I trial) and in patients with prolapse and occult stress incontinence (CUPIDO II trial). Methods/Design The CUPIDO trials are two multicenter randomized controlled trials in which women with stress urinary incontinence (SUI) or occult stress urinary incontinence (OSUI) are randomized to prolapse surgery combined with anti incontinence surgery (concomitant surgery) or to prolapse surgery only. Patients with at least stage 2 POP are eligible, women with evident SUI are randomized in CUPIDO I. Patients without SUI are eligible for CUPIDO II and will have urodynamic evaluation or a standardized redression test. Women with OSUI are randomized, women without OSUI are followed up but not randomized. The primary outcome measure is absence of SUI twelve months after surgery. Furthermore, economic evaluations are conducted, and the effectiveness of urodynamic investigation is evaluated against a non-invasive way to determine SUI in women with POP. A total of 450 women will be included in the study. Trial Registration Trial registration http://www.trialregister.nl NTRR 1197 en 1070